Dynamical processes and changes in metal structure induced by high power ion beams; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 42, iss. 3 - Chistjakov S. A. (1989, 1989)
Title screen